PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN MITRA TANI DI KABUPATEN KEBUMEN - Dwi Maulina (Jurnal Ilmiah Sultan Agung, 2022)
The purpose of this research to test and analyze: service quality on farmersatisfaction. Respondents in this study were farmers from the Mitra Tani Kiosk inUngaran Village, Kebumen Regency.The research applied the associative method with a quantitative approach that aimsto determine the relationship between two or more variables. With this research, atheory can be built that can function to explain, predict and control a symptom. Thevariables used are reliability, responsiveness, assurance, empathy, tangible andfarmer satisfaction. The analysis technique used is multiple linear analysis withprocessing aids, namely IBM SPSS version 26.The results show that reliability has a positive and significant effect on farmersatisfaction, responsiveness has a positive and significant effect on farmersatisfaction, assurance has a positive and significant effect on farmer satisfaction,empathy has no effect on farmer satisfaction, tangible has a positive and significanteffect on farmer satisfaction.